Ultra-high performance liquid chromatography (uhplc) method development and validation for the determination of serum imatinib and its active metabolite concentration among chronic myeloid leukemia patients - Liong, Tan Ka (2013)
A simple and sensitive method for the simultaneous detection of imatinib mesylate and its active metabolite, N-desmethylimatinib, in human serum samples was developed. Separation was successfully achieved using an Agilent® ZORBAX Eclipse plus Cis reversed phase column (50 x 2.1 mm, i.d.; 1.8 pm) under isocratic mobile phase conditions consisting of acetonitrile: 0.02 M potassium dihydrogen phosphate with 0.2% triethylamine added at pH 3 (25:75, v/v) and ultra-violet detection at 235 nm. Extraction of the target compounds was completed by a protein precipitation method using 100% cold acetonitrile. Good linearities (r2 > 0.99) for Ndesmethyhmafaob and imatinib mesylate were achieved for the concentration ranges of 50-360 ng/mL and 50-1800 ng/mL, respectively. The detection limits were 20 ng/mL and 10 ng/mL for N-desmethylimatinib and imatinib mesylate, respectively. The intra- and inter-day precisions were less than 1% while the percentage recoveries were more than 95%. The method was successfully applied to calculate the pharmacokinetic parameters of chronic myeloid leukemia patients receiving imatinib. For imatinib, mean Vd was 113.32 ± 43.52 L, CL was 5.012 ± 0.028 L and AUC was 62953.33 ± 9791.38 ng.h.L’1. For N-desmethylimatirab, mean Vd was 415.27 ± 228.72 L, CL was 4.84 ± 3.85 L and AUC was 5585.15 ± 2950.42 ng.h.L’1. The method is suitable to be routinely applied for determination of ZV-ctesTnetAyZimatinib and imatinib mesylate in serum.